Biochemical content variation in Arachis hypogaea under drought stress with or without paclobutrazol and ABA - K. Karthishwaran, R. Somasundaram, B. Sankar, P. Gopinathan (Journal of Ecobiotechnology, 2016)
An experiment was conducted to determine the changes in biochemical parameters (amino acid, protein and proline) under drought stress, paclobutrazol (PBZ) and abscisic acid (ABA) and their combination. Drought stress caused a significant increase in the biochemical constituents like amino acid and proline contents when compared with control in groundnut plants. PBZ and ABA treatment to the drought stressed plants also increased amino acid and proline contents. But these contents were lower than that of drought stressed plants. Paclobutrazol and ABA treatments to the drought stressed plants increased the protein content when compared to drought stressed plants. Increase drought tolerance induced by PBZ and ABA in groundnut will be helpful for the farmers to cultivate peanut under drought condition.